Teachers' information-seeking on accomplishments of academic tasks: A systematic review - Novian, Rayhan Musa (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2024)
Background of the study: Teachers have a vital role in education, which includes educating and guiding students, developing teaching materials, preparing lesson plans, and performing student evaluations. Therefore, individuals need information in order to complete their educational objectives. Purpose: This review aims to systematically examine the three constituent elements of information-seeking behavior, with a particular emphasis on their application within the teaching field. Method: The systematic literature evaluation in this study was guided by the PRISMA approach. The study's data collecting phase spanned a period of twenty years, specifically from 2003 to 2023. The study's results encompassed an extensive review of 25 research papers about the information-seeking behavior shown by educators. This review employed an inductive approach to data analysis. Findings: Teachers demonstrate a preference for selecting information sources that encompass digital, printed, and interpersonal types. Teachers prioritize information sources that are familiar, user-friendly, and have a well-designed interface. Teachers have several barriers when seeking information, which can be attributed to both internal and external constraints. Conclusion: This study draws on studies related to teachers' information behavior published in the last 20 years. Our goal is to comprehensively understand the information sources teachers use, their awareness of these sources of information, and the constraints they encounter when information-seeking.